Final Environmental statement[s on proposed national parks, monuments, wildlife refuges, etc.] Alaska - United States. Dept. of the Interior. Alaska Planning Group ([Washington] : The Department, 1974)
Includes bibliographies. Mode of access: Internet. Library has: v.1-27. [1] Proposed Alaska coastal national wildlife refuge -- [2] Proposed Arctic National Wildlife Refuge -- [3] Proposed Beaver Creek National Wild River -- [4] Proposed Cape Krusenstern National Monument -- [5] Proposed Chugach National Forest additions -- [6] Proposed Chukchi Imuruk National Reserve -- [7] Proposed Fortymile National Wild and Scenic River -- [8] Proposed Gates of the Arctic National Park -- [9] Proposed Harding Icefield-Kenai Fjords National Monument -- [10] Proposed Iliamna National Resource Range -- [11] Proposed Katmai National Park -- [12] Proposed Kobuk Valley National Monument -- [13] Proposed Koyukuk National Wildlife Refuge -- [14] Proposed Lake Clark National Park -- [15] Proposed Mt. McKinley National Park additions -- [16] Proposed Noatak National Arctic Range -- [17] Proposed Selawik National Wildlife -- [18] Proposed Togiak National Wildlife Refuge -- [19] Proposed Unalakleet National Wild River -- [20] Proposed Wrangell Mountain National Forest -- [21] Proposed Wrangell-St. Elias National Park -- [22] Proposed Yukon Delta National Wildlife Refuge -- [23] Proposed Yukon-Charley National Rivers -- [24] Proposed Yukon Flats National Wildlife Refuge -- [25] Proposed Yukon-Kuskokwim National Forest -- [26] Proposed Birch Creek National Wild River -- [27] Proposed Porcupine National Forest.